Tinjauan Kontekstual Atas Hadis-hadis Cadar: Argumentasi Pensyariatan Cadar dalam Islam - Nur Afni A.; Arfan, Arfan (JAWAMI'UL KALIM: Jurnal Kajian Hadis, 2024)
This study aims to analyze the hadiths on veiling in contextual examination to comprehend whether veiling represents an adopted Arabian custom or an Islamic injunction. Through library research utilizing normative and historical approaches, primary data was obtained from books of hadith and their commentaries. Secondary data was derived from classical tafseer and jurisprudential literature, as well as Arabic dictionaries. All data was compiled and analyzed to draw conclusions. The findings reveal that the scanty dressing of pre-Islamic Arabian women contravened the Islamic concept of hijab, hence veiling was not an Arabian cultural element. Quranic verses regarding hijab contain injunctions or recommendations for veiling. This was further corroborated by Prophetic narrations which contextually imply the legislation of veiling for Muslim women. Thus, a comprehensive study of scriptural evidence concludes that veiling constitutes part of the Islamic Shariah.